Variobox: Automatic Detection and Annotation of Human Genetic Variants. Issue 2 (21st November 2013) - Gaspar, Paulo; Lopes, Pedro; Oliveira, Jorge; Santos, Rosário; Dalgleish, Raymond; Oliveira, José Luís
<x xml:space="preserve">Abstract</x> Variobox is a new tool to support the sequence analysis workflow through the exploration of individual patient genes and their variants, taking advantage of available web‐sourced knowledge. The application obtains up‐to‐date information about a gene and its variants, and is able to align patient sequences with reference genes and automatically infer variant annotations using HGVS nomenclature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>